Design and Build an Automated School Bell System Using Voice-Based IoT - Khairul Abdi Azizi; Arnes Sembiring; Mili Arfisyari (CV. AFDIFAL MAJU BERKAH, 2022)
A tool for Designing an Automated School Bell System Using Voice-Based IOT has been designed. The system of this tool uses a NodeMCU ESP8266 microcontroller where the NodeMCU ESP8266 functions as a data processor, and also a WI-FI network receiver emitted by a WI-FI network system. This tool system uses a control system using an android smartphone to turn on the school bell, namely the entrance bell, the recess bell, and the home bell, this tool uses a WI-FI network communication system so that the device system and android smartphone can be connected, the system of this tool uses the ISD1820 module as an output connected to the speaker and the speaker functions to emit the sound of the bell on the designed tool system. The smart phone application used in the design of this tool is the BLYNK application which can be downloaded on playstore or google.com It is hoped that this tool can help and make it easier for teachers who are on duty in turning on the school bell